BOBATH THERAPY AS AN EARLY STROKE PREVENTION EFFORT - Imamatul Faizah; Niken Adiba Nadya; Dyah Yuniati; Ratna Yunita Sari; Yanis Kartini; Abdul Muhith; Riska Rohmawati (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
In ischemic stroke patients, the main problem that occurs is cerebral blood flow disturbances. Global Burden Disease data shows that 80% of the population is ischemic stroke and 20% hemorrhagic stroke with a moderate level of neurological deficit of 89%. Nursing actions that can be taken are by providing activities to stroke patients to increase cerebral blood flow. The implementation of this community service activity aims to teach Cadres and the community regarding Bobath Therapy as an early stroke prevention effort. The method used in this community service activity is to provide training and education health services. This activity was carried out during April-May 2022 which was attended by 12 health cadres and 22 residents in RW 06 Wonokromo Village, Surabaya. The results show that the activity has achieved success according to the success indicators that have been set, namely as many as 12 health cadres were successfully recruited; average attendance is 100%, participants participate in activities enthusiastically, knowledge of cadres after training and residents after counseling increases significantly